The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (The Cairo Regional Centre for International Commercial Arbitration, 2024)

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (Institute of Development Studies, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability